Syracuse and its environs from c. 6000 to 650 BC: the prehistoric and Greek origins of the city - Leighton, Robert (Journal of Greek Archaeology, 2020)
Scholars, as well as modern residents, might well agree with Cicero that Syracuse was ‘the richest and fairest’ of Greek cities in Sicily, where its pre-eminence is well attested by historical and archaeological evidence. The nature and form of the settlements which preceded Greek colonization, however, are much harder to evaluate and have never been the subject of a unified analysis or synthesis. Sealed under buildings and layers accumulated throughout nearly 3000 years of urban development, the remains of prehistoric and early Greek Syracuse are largely invisible today, although they have been uncovered periodically by archaeologists over the last century or more. This article offers a chronologically extended view of the city’s origins, which situates the island promontory of Ortygia within a regional settlement network encompassing the natural bay area (or great harbour) and its hinterland. Starting in the Neolithic, but with the focus on later periods, I assess the initial expansion of Greek Syracuse with reference to pre-existing spatial relationships and cultural adaptations, which began to take shape during the Bronze and Iron Ages.